2001
DOI: 10.1002/qre.409
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting engineering knowledge about reliability during design‐lessons learnt from implementation

Abstract: SUMMARYIn electronic design the use of engineering knowledge and experience is considered important in understanding and estimating the reliability performance of complex systems. There are numerous methods proposed for eliciting this knowledge in order to ensure that the data collected are valid and reliable. In this paper we describe our experiences in implementing an elicitation process that aims to extract engineering knowledge about the impact of design changes on a new aerospace product that is a variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…We seek to develop prescriptive decision support for project management in reliability development where well established protocols for eliciting expert subjective probabilities exist (see for example [3,36,15,22]). We do not make use of probability weighting functions which represent distortions of probabilities and as such our approach is consistent with classical utility theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We seek to develop prescriptive decision support for project management in reliability development where well established protocols for eliciting expert subjective probabilities exist (see for example [3,36,15,22]). We do not make use of probability weighting functions which represent distortions of probabilities and as such our approach is consistent with classical utility theory.…”
Section: Discussionmentioning
confidence: 99%
“…We can elicit both λ i and p i,j , by asking questions about observable quantities, from engineering experts inside the organisation. For more information see [15]. Similarly, [35] developed a Bayesian model based on observable quantities for reliability growth in the TAAF cycle.…”
Section: The Efficacy Matrixmentioning
confidence: 99%
“…The elicitation of probabilities to quantify the uncertainties represented in the model is informed by the recognized process of structured expert judgement as reported in, for example, Cooke (1991) and Quigley et al (2008) and drawing on our experiences as reported in Hodge et al (2001). The questions are determined by the dependencies captured in the influence diagram.…”
Section: Eliciting Probabilities Of Uncertaintiesmentioning
confidence: 99%
“…Two elicitation processes specific to reliability include PREDICT (Kerscher (1998(Kerscher ( , 2003 and REMM , Walls and Quigley (2001) and Hodge et al (2001)). Both provide modelling frameworks designed to estimate reliability throughout system development beginning with a problem structuring phase, which consists of eliciting a graphical representation of the relationship between the potential failure modes and the system reliability.…”
Section: )mentioning
confidence: 99%